Synthesis of Open-Cage Fullerenes with a Long Tail - Zhang, Hao; Su, Jie; Gan, Liangbing (Organic Materials, 2020)
To explore potential applications for open-cage fullerenes, we employed 4-((6-bromohexyl)oxy)aniline to react with an open-cage fullerene precursor which has an 11-membered orifice and prepared open-cage fullerenes with an 18-membered orifice. The bromo atom at the end of the hexyl chain in these open-cage compounds could be easily replaced by alkoxyl groups to further extend the linear chain. The results also show that the presence of the alkyl chain slightly changes the reactivity of the orifice-expansion reaction.
Keywords: fullerene; open-cage; amphiphilic